Tomorrow’s public hospital in Greece: Managing health care in the post crisis era - Minogiannis, Panos (Social Cohesion and Development, 2016)
The management of the hospitals (defined as the attempt for optimum performance via appropriate cycles of planning, deciding, evaluating, and reviewing), transcends all the functional parameters of the production and provision of health services. Tomorrow’s public hospital in Greece demands a new managerial approach. This approach would sufficiently answer to the main four problematic conundrum of today: the perverse unaccountability of medical subjectivity, the obsolete management model, the lack of human resources management tools and the unhealthy financing of hospitals. Tomorrow’s hospital would respect the autonomy of the medical profession while at the same time would demand scientific accountability, would utilize modern organizational tools to manage its human resources in order to produce effectively and efficiently quality services and finally would measure its performance on a case by case basis.